COMMUNITY CAPACITY ENHANCEMENT IN COMMUNITY BASED TOURISM (CBT) MANAGEMENT IN SONGKHLA, THAILAND THROUGH EDUCATION AND TRAINING: Indonesia - Pratiwi, Briliani Putri Pijar; Kartina, Alessandro; Wardhana, Firnanda Hady; Hartono, Gita Alya; Inez Tasya Brilliant; Muhammad Ilham Arrasyid; Nabila Putri Siswandini; Naufal Izzuddin; Naura Khalilah Sandrina; Raisa Jawda Azzam (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This community service aims to analyze the role of education and training in strengthening the capacity of communities in Songkhla City, Thailand, in managing the impacts of community-based tourism. Through qualitative methods including observation, document analysis, and Focus Group Discussion (FGD), this community service found that education and training programs have succeeded in improving community understanding and skills. In the Koh Yor Weaving community, the training provided enabled members to develop more innovative and attractive woven products for tourists, while maintaining local traditions. In the organic farming community, training encouraged the implementation of environmentally friendly agricultural practices that increased production sustainability. Meanwhile, the fishing community showed increased ability in natural resource management, reducing negative impacts on the environment. These findings confirm that education and training not only improve technical skills but also strengthen awareness of sustainable practices. In addition, active community participation in these programs shows a strong sense of ownership of the initiatives being implemented. Collaboration between the government, educational institutions, and non-governmental organizations is also an important factor in the success of these programs.